Positive selection of invariant V alpha 14+ T cells by non-major histocompatibility complex-encoded class I-like molecules expressed on bone marrow-derived cells. - Adachi, Y (1995)
V alpha 14+ T cells are a unique subset expressing an invariant T-cell antigen receptor alpha chain encoded by V alpha 14 and J alpha 281 gene fragments with a 1-nt N region. Most invariant V alpha 14+ T cells develop in extrathymic organs, independent of thymus, and expand at a high frequency in various mouse strains regardless of major histocompatibility complex (MHC) haplotype. In this paper, we show that the positive selection of invariant V alpha 14+ T cells requires a beta 2-microglobulin-associated MHC class I-like molecule not linked to the MHC on chromosome 17. This was determined by linkage analysis on DNA from recombinant mice generated by crossing a C57BL/6 mouse with a wild mouse, Mus musculus molossinus, that is negative for invariant V alpha 14 TCR expression. However, the peptide transporter TAP1 is not necessary for positive selection of invariant V alpha 14+ T cells, indicating the direct recognition of the MHC class I-like molecule without peptide by the invariant V alpha 14 TCR. Further, experiments with bone marrow-chimeric mice show that invariant V alpha 14+ T cells in the periphery are selected by bone marrow cells, suggesting a unique lineage of V alpha 14+ T cells differentiated through a selection process distinct from that of conventional alpha beta TCR+ T cells.